Kewenangan KPK dalam Melakukan Penggabungan Perkara TPPU dengan Predicate Crime Korupsi - Eki Tolanda; Estes Metelmety; Ragil Sanjaya Marjuki; Mulyadi Alrianto Tajuddin (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2024)
Crime is an act that can cause harm to other people and even to the state and is called a delict or criminal act which is regulated in the criminal code. The crime of money laundering (TPPU) is one of the criminal acts regulated in Law Number 8 of 2010. Several TPPU cases are crimes originating from corruption, so disclosure of these TPPU cases is carried out by the Corruption Eradication Commission (KPK). ). During the investigation and investigation process, the Corruption Eradication Committee found that the money resulting from corruption had been changed in form through the money laundering process, but in the process of enforcing the court's decision, it only decided on criminal acts of corruption even though money laundering had been carried out. The aim of the research is to determine the authority of the Corruption Eradication Committee (KPK) in combining TPPU cases with the predicate crime of corruption. The research method used is normative juridical. The results of the research can be concluded based on articles 74 and 75 of the TPPU Law which state that investigators of predicate crimes can carry out TPPU investigations if they find sufficient initial evidence of TPPU occurring when conducting predicate crime investigations in accordance with their authority so that the Corruption Eradication Commission is one of the investigators referred to based on the explanation in article 74 In terms of prosecution, it can be carried out by a public prosecutor from the Prosecutor's Office and a public prosecutor from the Corruption Eradication Commission if the original crime was corruption